2003
DOI: 10.1046/j.1365-2036.2003.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of KRAS mutational analysis in the diagnosis of pancreatic adenocarcinoma by means of endosonography‐guided fine‐needle aspiration biopsy

Abstract: SUMMARYAim: To establish the usefulness of KRAS mutational analysis in the diagnosis of pancreatic adenocarcinoma by comparing this technique with conventional cytology in aspirates obtained by endosonography-guided fine-needle aspiration. Methods: All consecutive patients with pancreatic focal lesions undergoing endosonography-guided fine-needle aspiration were included. Samples were obtained with the concourse of an attendant cytopathologist. Detection of codon-12 KRAS mutations was performed by the restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 26 publications
(72 reference statements)
1
26
0
2
Order By: Relevance
“…Several authors suggested that K-ras mutation analysis of EUS-FNA specimens is valuable. 16,[23][24][25][26][27][28] However, published reports have included relatively small numbers of patients with PDAC and other pancreatic tumors for comparison (Table 5). Here, we prospectively investigated the most patients in a single study to date and examined other pancreatic diseases for a differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors suggested that K-ras mutation analysis of EUS-FNA specimens is valuable. 16,[23][24][25][26][27][28] However, published reports have included relatively small numbers of patients with PDAC and other pancreatic tumors for comparison (Table 5). Here, we prospectively investigated the most patients in a single study to date and examined other pancreatic diseases for a differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…La spécifi-cité est assez élevée (entre 90 et 100 %), ce qui permet d'assurer le diagnostic de bénignité des masses pancréatiques. Plusieurs études, incluant celle menée par notre équipe, ont évalué l'importance de la recherche de la mutation de Kras dans le matériel de cytoponction pancréatique pour le diagnostic d'adénocarcinome (Tableau II) [20,[23][24][25][26]. Cette analyse apporte, tout d'abord, une contribution au diagnostic différentiel entre cancer et pancréatite chronique pseudotumorale.…”
Section: éTudes Sur Le Matériel De Ponction Pancréatiqueunclassified
“…Additionally, it has also been shown that the presence of an attending cytopathologist during the procedure is cost-effective; however, the availability of an onsite cytopathologist is a major issue. 12,13 The strategy used in our study, having an on-site cytotechnologist just to interpret adequacy, seems like an attractive approach. In institutions in which this is unavailable, an alternative may be to have an experienced endosonographer assess the cytological ade- Information was unavailable for the following variables: onsite pathology (n ϭ 23), number of biopsy specimens taken (n ϭ 1), needle gauge (n ϭ 2), and pathologist (n ϭ 1).…”
Section: Discussionmentioning
confidence: 99%